Acute Hemolytic Transfusion Reaction by an Anti-s Due to Delayed Type and Screen Procedures Until Occurrence of a Hemorrhagic Shock - Zimmermann, Robert; Strasser, Erwin; Hackstein, Holger (Transfusionsmedizin, 2019)
In the past decade, profound changes in the clinical practice of haemotherapy have occurred in most industrial countries, including Germany. Red blood cell (RBC) order procedures are performed more and more cautious. The utilization of RBC concentrates is strongly declining. At the same time, the number of patients for whom the preoperative or pre-interventional provision of cross-matched blood is not carried out despite planned surgery or intervention is also increasing. We report on a 71-year-old multimorbid patient with dilated cardiomyopathy, severely reduced cardiac reserve, a few weeks after valve replacement surgery, ongoing anticoagulation with heparin and diagnosed anemia with hemoglobin values between 7 and 8 g/dl. In this patient, a haemorrhagic shock was induced by a Forrest-II b haemorrhage from a duodenal ulcer after several days of in-patient treatment. In the context of emergency care, it turned out that all pre-transfusion diagnostics had been missed. The patient received uncross-matched red blood cell concentrates of blood group 0 Rh negative which unexpectedly triggered an acute haemolytic transfusion reaction. The reason was an irregular antibody against the antigen s from the MNSs blood group system that had not been identified before the transfusion. Acute hemolytic transfusion reactions outside the AB0 system are a rare, but nevertheless always threatening complication of the transfusion of uncrossmatched erythrocyte concentrates in life- threatening bleeding emergencies. The case shows that the desire to follow a restrictive transfusion practice must not lead to overlooking constellations in individual cases which, of course, require the timely performance of a pre-transfusional diagnostic procedure with blood group typing, antibody screening and antibody identification. In our opinion, the frequency of comparable events is increasing to an extent that suggests that such errors in the clinical treatment process should not only be dealt within CIRS systems but also recorded in haemovigilance systems.
CRIS-Team WoS Importer:2019-09-20